Palgrave Advances in Global Governance
XV, 207 p.
Keywords: Palgrave Advances in Global Governance is an authoritative collection devoted to clarifying established understandings of global governance as a distinct form of political activity. Ranging across the actors, arenas, means and purposes of global governance, this incisive collection brings order and clarity to a burgeoning literature.